A paper on the shortcomings of indian anesthesiology - SHREE MUKILAN PARI,; SREE LATHA HARI, (International Journal of Pharma and Bio Sciences, 2019)
The profuseness of anesthetic risk factors are exceedingly prevalent in India, thus, steps must be taken to address these problems. An exhaustive anesthetic literature analysis has indicated that previous research has identified areas of improvement but has not comprehensively summarized these issues and has not provided effective solutions to the following issues. The three largest areas that necessitate immediate improvement are the educational system of India, equipment used in many Indian hospitals, and access to safe anesthetic care for all Indians. In terms of the educational system, this is specifically in regards to the post-graduate education of anesthesiologists. This paper examines the effectiveness of problem-based learning (PBL) in comparison to the status quo lecture-based learning (LBL) method that has been utilized for decades in a majority of higher education medical institutes in India. Secondly, this paper examines poor quality of the equipment used in many Indian hospitals and recommends strategies to deal with that issue. Third and finally, with respect to the issue of access to safe anesthetic care for all, this paper explores a method for increasing access to all. The reason why India should start with the amelioration of anesthetic problems first is because it is the gateway to remedying other problems that afflict India in terms of health care, reduction of mortality, and improvement of the quality of life for all. Utilizing the solutions this paper recommends for solving the most basic problems will facilitate public health research’s focus to shift to pressing issues such as the aforementioned.